2021
DOI: 10.1021/acsnano.0c10341
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Luminescent Defects in Carbon Nanotubes with Covalently Attached Stable Organic Radicals

Abstract: The functionalization of single-walled carbon nanotubes (SWCNTs) with luminescent sp 3 defects has greatly improved their performance in applications such as quantum light sources and bioimaging. Here, we report the covalent functionalization of purified semiconducting SWCNTs with stable organic radicals (perchlorotriphenylmethyl, PTM) carrying a net spin. This model system allows us to use the near-infrared photoluminescence arising from the defect-localized exciton as a highly sensitiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 68 publications
(155 reference statements)
0
26
0
4
Order By: Relevance
“…[25,172] The notion of using the ratio of the E 11 to defect (E 11 * or E 11 * -) emission intensity as a measure for additional nonradiative decay channels close to the sp 3 defects was further explored by Berger et al with polymer-wrapped (6,5) SWCNTs that were covalently functionalized with the stable perchlorotriphenylmethyl (PTM) radical via diazonium chemistry. [173] The neutral open shell system of the PTM substituent at the sp 3 defect resulted in lower defect emission as well as shorter fluorescence lifetimes compared to nanotubes with the same number of defects but with a bromoaryl substituent. Again, the emission wavelengths were very similar.…”
Section: (9 Of 14)mentioning
confidence: 97%
See 1 more Smart Citation
“…[25,172] The notion of using the ratio of the E 11 to defect (E 11 * or E 11 * -) emission intensity as a measure for additional nonradiative decay channels close to the sp 3 defects was further explored by Berger et al with polymer-wrapped (6,5) SWCNTs that were covalently functionalized with the stable perchlorotriphenylmethyl (PTM) radical via diazonium chemistry. [173] The neutral open shell system of the PTM substituent at the sp 3 defect resulted in lower defect emission as well as shorter fluorescence lifetimes compared to nanotubes with the same number of defects but with a bromoaryl substituent. Again, the emission wavelengths were very similar.…”
Section: (9 Of 14)mentioning
confidence: 97%
“…Reproduced with permission. [173] Copyright 2021, The Authors, published by American Chemical Society under the terms of the Creative Commons BY-NC-ND 4.0 license.…”
Section: (9 Of 14)mentioning
confidence: 99%
“…Luminescent defects (or organic color centers) 7 have expanded the emission range of SWNTs further toward the near-infrared and opened up applications in sensing 14,15 , in vivo imaging within the second biological window 16,17 , and as quantum-light sources with room-temperature single-photon emission [18][19][20][21][22] . Various synthetic methods (e.g., radical-based reactions with aryl diazonium salts) allow for different functional groups to be attached to the SWNTs, which lead to additional small energetic shifts 18,[23][24][25][26] . However, defect emission in general occurs over a wide spectral range (e.g., from 1100 to 1350 nm for (6,5) SWNTs).…”
mentioning
confidence: 99%
“…closer to standard telecom wavelengths, advancing the prospects of applications as single-photon sources in quantum information processing [61]. Berger and co-workers [62] reported that a net spin can be carried out using the covalent functionalization of purified semiconducting SWCNTs with stable organic radicals (perchlorotriphenylmethyl, PTM). Their results confirmed the fact that the existence of the radical-enhanced intersystem crossing leads to an increased triplet exciton population, which could provide access to elusive triplet manifold in SWCNTs [62].…”
Section: Carbon Nanotubesmentioning
confidence: 99%